University hospitals, general hospitals, private clinics: Place-based differences in patient characteristics and outcomes of AF—A SAKURA AF Registry Substudy. Issue 1 (January 2020) - Kogawa, Rikitake; Okumura, Yasuo; Yokoyama, Katsuaki; Matsumoto, Naoya; Tachibana, Eizo; Kuronuma, Keiichiro; Oiwa, Koji; Nishida, Toshihiko; Matsumoto, Michiaki; Kojima, Toshiaki; Hanada, Shoji; Nomoto, Kazumiki; et al.
Highlights: Atrial fibrillation (AF) patients at a private clinic are older than at a university/general hospital. Strokes appear to be lower in clinic patients than in other hospital patients. Patients at a clinic have lower cardiovascular events than at other hospitals. Our data provide new insights into the clinical management of AF patients. Abstract: Background: Relations between characteristics and outcomes of patients in Japan with atrial fibrillation (AF) and the type of medical facility providing their outpatient care are unclear. Methods and results: We compared patient characteristics and outcomes between 2 university hospitals ( n = 1178), 20 general hospitals ( n = 1308), and 41 private clinics ( n = 751) (follow-up: 39.3 months) in the prospective SAKURA AF Registry. Private clinic patients were significantly older than university hospital and general hospital patients (73.4 ± 9.2 vs. 70.3 ± 9.8 and 72.6 ± 8.9 years; p < 0.001), and these patients' CHADS2 scores were significantly lower than general hospital, but higher than university hospital patients (1.8 ± 1.1 vs. 2.0 ± 1.2 and 1.6 ± 1.1; p < 0.001). The Kaplan–Meier incidences of stroke/systemic embolism (SE) (1.72 vs. 1.58 vs. 0.84 events per 100 patient-years; p = 0.120), a cardiovascular event (4.09 vs. 2.44 vs. 1.40; p < 0.001), and death were higher (2.39 vs. 2.21 vs. 1.24; p = 0.015) for university and general hospital patients than for private clinic patients; the incidences of major bleeding were equivalent (1.78 vs. 1.33 vs. 1.16; p = 0.273). After multivariate adjustments, this trend persisted. Conclusions: Adverse clinical events at small to large hospitals appear to be higher than those at private clinics, suggesting that careful attention for preventing stroke/SE and cardiovascular events should be paid to patients at a university or general hospital.